Negative Responses of Wetland Plant Species to Warming Linked to Temperature Artifacts - Wang, Hang; Li, Hui; Xu, Junping; Tian, Kun (Frontiers in Ecology and Evolution, 2020)
Empirical records of plant responses to climate warming increasingly rely on warming experiments which supposedly provide meaningful predictions of future scenarios. However, the accuracy of such predictions may be compromised by warming artifacts. In our study, we integrated two approaches, the use of in-situ open-top chambers (OTCs), as well as transplants along a latitudinal gradient, to study the biological responses of three wetland species to experimental warming over 4-5 years. Under ongoing warming, plant photosynthesis was negatively influenced by the OTCs, coupled with reduced species height and biomass accumulation, while unexpectedly, these trends were not reflected in the transplant experiments. Temperature patterns artificially altered with the use of OTCs included asymmetrical day/night warming and hot extreme events. To understand whether the significant mismatches in results between these two approaches could be attributed to these temperature alterations, we alleviated temperature artifacts by using two identical chamber types differing only in their opening sizes and making comparisons between these chambers. The negative impact of warming associated with the use of OTCs on wetland species was reversed when these temperature artifacts were canceled out, and consistent plant responses to warming were observed for both approaches. We highlight here, beyond the commonly-investigated reductions in soil moisture, that unintended temperature artifacts associated with the use of warming devices are major determinants of the negative responses to warming for wetland plant species.